The Value of Socialized Medicine: The Impact of Universal Primary Healthcare Provision on Birth and Mortality Rates in Turkey - Resul Cesur; Pınar Mine Güneş; Erdal Tekin; Aydogan Ulker (Institute for the Study of Labor (IZA), 2015)
This paper examines the impact of universal, free, and easily accessible primary healthcare on population health as measured by age-specific birth and mortality rates, focusing on a nationwide socialized medicine program implemented in Turkey. The Family Medicine Program (FMP), launched in 2005, assigns each Turkish citizen to a specific state-employed family physician, who offers a wide range of primary healthcare services that are free-of-charge. Furthermore, these services are provided at family health centers, which operate on a walk-in basis and are located within the neighborhoods in close proximity to the patients. To identify the causal impact of the FMP, we exploit the variation in its introduction across provinces and over time. Our estimates indicate that the FMP caused large declines in mortality rates across all age groups with more pronounced impacts among infants and the elderly, and a moderate reduction in the birth rates, primarily among teenagers. Furthermore, the results are suggestive that the program has also contributed towards equalization in the mortality disparities across provinces. Our findings highlight the importance of a nationwide supply-side intervention on improving public health.
Keywords: I0; I1; I11; I13; I14; I18; J13; J14; 330; healthcare; reform; socialized; medicine; health; Turkey; infant; mortality; birth; teenager; physician